THE AESTHETICS OF JEPARA CARVING ON TEAK WOOD CHAIRS AS A FORM OF CREATIVITY AND SKILL OF LOCAL CRAFTSMEN - Tasya Maqsida; Wasis Wijayanto (Universitas Negeri Semarang, 2025)
Jepara carvings on teak chairs are an Indonesian cultural heritage known internationally for their beauty and quality craftsmanship. This study aims to analyze the aesthetics of Jepara carvings on teak chairs and identify the creativity and skills of local craftsmen in developing carving motifs. The study used a qualitative method with a case study approach conducted in Jepara Regency, Central Java. Data collection was conducted through observation, interviews with craftsmen, and documentation. Data analysis used the Miles and Huberman model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results show that the aesthetics of Jepara carvings are evident in the beauty of intricate and detailed motifs, inspired by flora and fauna, with harmonious proportions and compositions. Motifs such as lung-lungan, patran, and truntum not only function as decorative elements but also contain philosophical meanings that reflect the culture and spirituality of the Javanese people. The craftsmen's creativity is reflected in their ability to innovate and create new motifs without losing their traditional identity. The craftsmen's skills are formed through a long learning process passed down from generation to generation, requiring years of dedication. Despite facing the challenges of modernization, Jepara craftsmen maintain the aesthetic quality and traditional values in each of their works.